Q: What is the square root of 24 minus square root of 6?

Write your answer...

Submit

Related questions

The square root of -24 is the same thing as the square root of -1, times the square root of 24. So, the square root of -1 is called 'i'. and the square root of 24 is equal to 2 times the square root of 6. Therefore, the square root of -24 is equal to: 2i* square root of 6.

9 square root 4 minus 12 square root 4 = -6

Square root 400 - square root 196 = 6

X2+5x-6. a=1, b=5, and c=-6 The formula is: -b plus or minus the square root of b squared minus 4ac all over 2a. -b+square root of b2-4ac ---- 2a -5 plus or minus the square root of 5 squared minus 4(1)(-6) -5 plus or minus the square root of 25-4(-6) -5 plus or minus the square root of 25+24 -5 plus or minus the square root of 49 -5 plus or minus 7 Here is where you split into two different answers: Number 1: -5 plus 7= 2 Number 2: -5 minus 7= -12 Your answer is X=2, -12

The idea is to take any perfect square out of the square root sign. root(24) = root(4 x 6) = root(4) x root(6) = 2 x root(6).The idea is to take any perfect square out of the square root sign. root(24) = root(4 x 6) = root(4) x root(6) = 2 x root(6).The idea is to take any perfect square out of the square root sign. root(24) = root(4 x 6) = root(4) x root(6) = 2 x root(6).The idea is to take any perfect square out of the square root sign. root(24) = root(4 x 6) = root(4) x root(6) = 2 x root(6).

It is the square root of 8

Yes and x = 2+square root of 6 or x = 2-square root of 6

sqrt(24) / sqrt(6) = sqrt(24/6) = sqrt(4) = Â±2

It depends on whether you take the positive square root of 4 (YES) or the negative square root of 4 (No).

The numbers are: 6 plus square root of 27 and 6 minus square root of 27

6

plus or minus 6

0.6667

8

Could be +6, -6, +16, or -16.

8*6**0.5 - 2*24**0.5 24**0.5= 4**0.5 * 6**0.5 24**0.5= 2*6**0.5 8*6**0.5 - 2*2*6**0.5 8*6**0.5 - 4*6**0.5 4*6**0.5

square root of 36 = 6 6 multiplied by 6 = 36 formula -> x2 = 36 (take square root of both sides) -> x = plus/minus 6

Sqrt 24 = Sqrt 4 x Sqrt 6 = 2 x Sqrt 6, 2 Root 6

24 = 4 x 6 so sqrt 24 = sqrt 4 x sqrt 6 = 2 root 6

24 = 4*6So sqrt(24) = sqrt(4*6) = 2*sqrt(6) and so sqrt(-24) = +/- 2*sqrt(6)*i where i is the imaginary square root of -1.

Yes. √6 + √24 = √6 + √(4 x 6) = √6 + 2√6 = 3√6 (= √54)

It is 24*sqrt(6)

To find the RMS or root mean square, we first square the numbers then add the squares. So for 6 and 24 the sum of the squares is 612 Now we divide by n which is the 2 in this case so 612/2=306 and take the square root of that.=3xsquare root of 24 or about 17.4929

2√6

It is 2*sqrt(6).

Study guides